Barong Using Optimalisasi Seni Pertunjukan sebagai Obyek Pariwisata Budaya Using - Muhammad Agung Pramono Putro; Bambang Soepeno; Rully Putri Nirmala P (Sabda: Jurnal Kajian Kebudayaan, 2019)
Barong Using is a performance art which is native to the Using community. Barong Using is used as a sacred necessity for clean village rituals. Rituals are held twice a year. The Ider Earth Ritual on the 2nd of Shawwal and the moon village salvation ritual were recited. The cultural development of bringing the art of barong performance functions as a sacred and profane need. There are efforts to optimize the art of barong performance by the use of tourism. The problems contained in this study are related to discussing (1) the history of Barong Kemiren's performance in which it examines ritual processions with socio-cultural values; and (2) efforts to optimize the art of barong performance later using communities in 1996-2018 as the use of tourism. The research method used is the historical research method by using a cultural anthropology approach to study cultural change and using structural functionalism theory to analyze the shift in barong function socially as a result of tourism. The results of this discussion, the optimization of the art of barong performance is packaged in the interrelationships of the five pillars that support the development of tourism and creative industries, namely, the state, art and ritual actors, supporting communities, industry, and religious leaders. These pillars can provide the right input so that a good response emerges from entrepreneurs, bureaucrats, cultural practitioners, and practitioners of traditional and ritual arts. Now the art of barong performance has undergone many changes starting from the structure of performances and interludes which accompany.